Perancangan Aplikasi Daftar Menu Restaurant Dan Food’s Cemara No.17 Menggunakan QR-Code Berbasis Website - Alfin Danu Ardianto; Mochamad Adhari Adiguna (CV. Multi Kreasi Media, 2023)
Dan Food’s is a bussines that is engaged in food and baverage culinary, based on the analysis carried out, it is known that the menu ordering system at Dan Food’s restaurant which is culinary running is still not optimal and there are still problems such as cstomers having to approach the cashier to place order or make payments, the author find solution to this problem in the form making and ordering application using a QR Code based on the customer website, it is only enough to scan the QR Code that has been provided by the restaurant, customers can immediately see the available menus and can also directly make without having to approach the cahsier. The need for a QR Code (Quick Response Code) is the development of a Bar-Code which was once a dimensional exclamation code into a two-dimensional code with the abilility to store data large than the Bar Code, by using a QR Code the data that can be stored an be in the form of a number code, letters, binary, and kanji, this code has been appliedin varios regions. One of the uses of QR Code is a medium for promortionfor store, because by using this code and with the help of the internet, a promortion system will low cosh cover a very wide area. This process make it easier for customers find the menu they want because they don’t need to approach the cashier, let alone wait in line, but simply scan the QR Code.